PENGARUH LIABILITAS JANGKA PANJANG DAN OPERASIONAL COST TERHADAP NET PROFIT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Kamaludin, Nurhadi; Ristiyana, Wiwit (Jurnal Riset Keuangan dan Akuntansi, 2023)
The purpose of this research is to understand the influence of long-term liabilities and operational costs on net profit in manufacturing companies listed on the Indonesian Stock Exchange (BEI) from 2017 to 2021. This research is a quantitative descriptive study, which involves numerical data. The sample size for this study consists of 11 companies out of a total population of 17, resulting in a total of 55 financial reports as samples. In practice, this research uses SPSS 21 software, and the data analysis technique employed is multiple linear regression analysis. The t-test results show that long-term liabilities significantly affect net profit with a significance level of 0.041. Similarly, operational costs significantly impact net profit with a significance level of 0.000. The results of the F-test indicate that long-term liabilities and operational costs collectively influence net profit significantly at a significance level of 0.000. The coefficient of determination test results show that 91% of the variability in net profit can be explained by long-term liabilities and operational costs, while the remaining 9% is explained by other variables.